Implementation of Multicultural Education through Differentiated Learning: A Case Study at Play Ground - Masarudin, Budi Alif; Prihatin, Yoga; Maufur, Maufur (Journal of English Language and Education, 2025)
This study aims to examine the implementation of Multicultural Education through Differentiated Learning in KB Dabin Cahaya, Bojong District, Tegal Regency. This qualitative research analyses the teachers' and managers' understanding of the two concepts, the supporting and inhibiting factors for their implementation, and the impact on students' learning achievement. The results show that teachers and managers have a good understanding of both concepts, but there are still obstacles such as lack of training and resources. Differentiated learning is proven effective in improving students' learning motivation, concept understanding, social skills, self-confidence and critical thinking. This study concludes that the implementation of differentiated learning in the context of multicultural education has great potential in shaping students' characters that are tolerant, respect differences and have good learning achievements.